The application of technology to the processing of dry-salted fish in peninsular Malaysia: comparison of sun-dried and oven-dried fish - Yu, S. Y.; Siaw, C. L.; Idrus, Zulkifli (Institute of Food Science and Technology, 1982)
Investigation of processing of dry-salted fish is described. The use of a satisfactory ratio of salt to fish, optimization of salting time and the use of mechanical driers to reduce drying time, insect infestation and microbial spoilage were investigated. Results indicated that oven-dried fish salted at 10% and 20% levels were most acceptable. The corresponding sun-dried samples had an undesirable odour, flavour and texture due to their higher moisture contents. At the 30% and 40% salt levels for both processes, the differences were less pronounced, but the samples that were sun-dried were more acceptable mainly as a result of a better appearance.